Evaluation of the surgical outcome and complications of total laparoscopic hysterectomy in patients with enlarged uteruses. (December 2016) - Terzi, Hasan; Hasdemir, Pinar Solmaz; Biler, Alper; Kale, Ahmet; Sendag, Fatih
Abstract: Objective: The aim of this study was to investigate whether uterine weight has a deleterious effect on the operation time, complication rates, length of hospital stay and incidence of intraoperative haemorrhage during total laparoscopic hysterectomy operation. Methods: A total of 282 patients who underwent total laparoscopic hysterectomy for benign gynaecologic indications were retrospectively analyzed. The median operation time of 70 min was accepted as an index number, and a cut-off point of ≥300 g was calculated for uterine weight by using reciever operator characteristics (ROC) curve analysis. Results: There was no statistically significant relationship between the uterine weight and haemoglobin drop rate (1.27 ± 0.89 vs 1.21 ± 0.88, p = 0.905), complication rate (10.83% vs 9.26%, p = 0.062) and length of hospital stay (3.27 ± 1.23 vs 3.37 ± 1.35 days, p = 0.505) based on this cut. Lee-Huang point was preferred for abdominal entry in cases with uteruses reached the level of umbilicus −2 cm in physical examination. Conclusions: Uterine weight was not effected the complication rate, estimated blood loss and length of hospital stay in total laparoscopic hysterectomy operation. A cut-off value of 300 g could be used for an increased operation time. Highlights: Hysterectomy, a common gynaecological procedure performed throughout the world. Total laparoscopic hysterectomy (TLH) has benefits such as early recovery, less postoperative pain, shorter hospital stay. Uterine weight does not affect the complication rate, estimated blood loss and length of hospital stay in TLH operation. A cut-off value of 300 g for uterine weight could be used for a longer operation time.